2007
DOI: 10.1002/pssc.200674355
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ag‐Cu nanoparticles in SiO2 films by sol‐gel process and their effect on the film properties

Abstract: Sol-gel thin films and microcrystalline powders of SiO 2 doped with Ag and Cu were obtained under environmental conditions of pressure and temperature. The precursor material was a mixture of water, tetraethyl-orthosilicate, ethanol and aqueous solutions of Ag and Cu salts, the components were taken in ratios known to provide SiO 2 matrix material with good structure. The annealing was performed in oxidizing and reducing atmosphere, the temperature varied in the range of 100 -800 °C. Formation of metal particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the same way recently our research group has reported the crystallization of SiO 2 sol-gel made with the introduction of the metal nitrates in the starting solution, Ag, Cu and mixtures of Ag and Cu [9,10,11,12] obtaining low temperatures of crystallization, 600 ºC for quartz in the mixture with AgNO 3 and (Cu(NO 3 ) 2 ) and 500 ºC for the α-cristobalite with the introduction of AgNO 3 .…”
Section: Introductionmentioning
confidence: 56%
“…In the same way recently our research group has reported the crystallization of SiO 2 sol-gel made with the introduction of the metal nitrates in the starting solution, Ag, Cu and mixtures of Ag and Cu [9,10,11,12] obtaining low temperatures of crystallization, 600 ºC for quartz in the mixture with AgNO 3 and (Cu(NO 3 ) 2 ) and 500 ºC for the α-cristobalite with the introduction of AgNO 3 .…”
Section: Introductionmentioning
confidence: 56%
“…According to the model suggested by L. L. Díaz-Flores et al, the near-to-metal atoms of a matrix will be in the vibrational state much different from the bulk atoms. This vibrational energy is sufficient to break the inter-atomic bonds, thus disrupting the amorphous network and reducing the kinetic barrier to the crystallization 21,22 .…”
Section: Crystallization Of Silver and Silicamentioning
confidence: 99%
“…Jeon et al [118] prepared silver-doped TEOS-derived silica thin films by the sol-gel method, showing an antibacterial effect against Escherichia coli and Staphylococcus aureus. Díaz-Flores et al [119] prepared antibacterial TEOS-derived solgel thin films and microcrystalline powders doped with Ag and Cu.…”
Section: Biocidal Sol-gel Coatingsmentioning
confidence: 99%